Pastoral penality in 1970s Ireland: Addressing the pains of imprisonment - Brangan, Louise (Theoretical criminology, 2021)
This article aims to deepen and broaden our US- and UK-centric theories and histories of late 20th-century penal transformation. Using oral history interviews with civil servants, archival research and analysis of published documents, this article investigates Ireland’s delayed progressive penal transformation in the 1970s. It challenges the dominant narrative that Irish penal policy was stagnant or merely pragmatic during this period and provides cultural, social and political explanations for Ireland’s changing penal culture. These findings also show the limitations of penal welfarism for sufficiently capturing the character of Ireland’s progressive penal ideas and intentions. The article outlines the concept of pastoral penality as an alternative kind of progressive penal politics. Pastoral penality focuses on the problems of the prison, rather than the problems of the prisoner, who is not viewed as inherently criminal and in need of treatment. Instead they require support in coping with the harms of imprisonment.